2001
DOI: 10.1051/0004-6361:20010495
|View full text |Cite
|
Sign up to set email alerts
|

The second ROSAT PSPC survey of M 31 and the complete ROSAT PSPC source list

Abstract: Abstract. This paper reports the results of the analysis of the second ROSAT PSPC survey of M 31 performed in summer 1992. We compare our results with those of the first survey, already published in Supper et al. (1997). , distributed approximately equally between the bulge and disk. Within the bulge region, the luminosity of a possible diffuse component combined with faint sources below the detection threshold is (2.0 ± 0.5) × 10 38 erg s −1 . An explanation in terms of hot gaseous emission leads to a maximum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
187
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 123 publications
(205 citation statements)
references
References 28 publications
(33 reference statements)
16
187
2
Order By: Relevance
“…A ROSAT PSPC mosaic of 6 contiguous pointings with an exposure time of 25 ks each was performed in July 1991 (first M 31 survey; Supper et al 1997, hereafter SHP97). A second survey was made in July/August 1992 and January and July 1993 (Supper et al 2001. Several SSS candidates were identified.…”
Section: X-ray Detection Of Optical Novae In M 31mentioning
confidence: 99%
“…A ROSAT PSPC mosaic of 6 contiguous pointings with an exposure time of 25 ks each was performed in July 1991 (first M 31 survey; Supper et al 1997, hereafter SHP97). A second survey was made in July/August 1992 and January and July 1993 (Supper et al 2001. Several SSS candidates were identified.…”
Section: X-ray Detection Of Optical Novae In M 31mentioning
confidence: 99%
“…The most extensive study of supersoft sources in an external spiral galaxy similar to our own and M81 is the ROSAT survey of M31 (Supper et al 1997;Kahabka 1999). Based on hardness ratios, Supper et al (1997) identified 15 supersoft source candidates not associated with supernova remnant (SNR) or foreground objects in a 6.3 deg 2 M31 field.…”
Section: Observations Of Other Galaxiesmentioning
confidence: 99%
“…Based on hardness ratios, Supper et al (1997) identified 15 supersoft source candidates not associated with supernova remnant (SNR) or foreground objects in a 6.3 deg 2 M31 field. Kahabka (1999), using a slightly modified selection criteria, identified an additional 26 candidates in the field.…”
Section: Observations Of Other Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations of sources in the Milky Way and Local Group galaxies show that many of the brightest X-ray sources are high-and low-mass X-ray binaries (HMXBs, LMXBs), but there are also sources associated with supernova remnants (SNRs) and H ii regions. For example, the ROSAT survey of M31 (Supper et al 2001) revealed a total of 560 X-ray sources, 16 of which have been optically identified with SNRs and 33 with globular clusters. Most of the bulge sources in M31 have been identified on the basis of their X-ray spectra as low-mass X-ray binaries (Trinchieri et al 1999;Primini, Forman, & Jones 1993).…”
Section: Introductionmentioning
confidence: 99%